IN THE SERVICE OF A “PURE IDEAL”: GANDHI, INDIAN NATIONAL CONGRESS AND THE DENIAL OF THE ARMENIAN GENOCIDE - Nagothu, Naresh Kumar (Armenian Folia Anglistika, 2025)
Determined to reverse the impending disintegration of the Ottoman Empire after the First World War, South Asian Muslims launched the Khilafat movement (1919-1924). Realizing that this issue had galvanized Muslims like no other, Gandhi saw the movement as a rare opportunity to unite Hindus and Muslims and offered unwavering support. This support was premised on the denial of the Armenian genocide. Legitimated in South Asia post-independence (1947) through historiographies, foreign policy and commemorative practices, this historical episode has transitioned into a mnemonic regime. This positive memorialization in South Asia has been extremely useful for Turkey in furthering its narratives of denial leading to a transregional mnemonic landscape that is premised on occlusion and justification of violence against the Armenians. While existing scholarship has briefly remarked on Gandhi’s denial, using a range of primary sources, including unpublished letters, this article shows the far more expansive role Gandhi played along with the Indian National Congress in mainstreaming a network of genocidal apologia and denial. Examining the absence of any detailed work on this denialism even after a century, this article also deals with the blind spots of postcolonial studies and the complicity of South Asia academia in perpetuating hegemonic narratives.
Keywords: Armenian Genocide; Gandhi; Indian National Congress; Khilafat Movement; South Asia; Denial